Hyperglycemia effect on coronary disease in patients with metabolic syndrome evaluated by intracoronary ultrasonography. - Beatriz Dal Santo Francisco Bonamichi; Erika Bezerra Parente; Ana Carolina Noronha Campos; Adriano Namo Cury; João Eduardo Nunes Salles (PLoS ONE)
Introduction Metabolic syndrome (MS) is characterized by dyslipidemia, central obesity, hypertension and hyperglycemia. However, type 2 diabetes mellitus (T2DM) may or may not be present in metabolic syndrome. MS and T2DM are considered important cardiovascular risk factors, but the role of hyperglycemia in coronary disease is still contested in the literature. Therefore, we decided to evaluate the effect of hyperglycemia on the severity of coronary disease in MS patients, with or without T2DM, submitted to coronary angiography (CA) and intravascular ultrasonography (IVUS). Materials and methods This is a cross sectional, observational study with 100 MS patients (50% with T2DM), 60% male. All of the patients had been referred for CA procedures. The obstruction was considered severe when stenosis was greater than 70% and moderate if it was between 50-69%. Patients detected with a moderate obstruction by CA were indicated to IVUS. A minimal luminal area of less than 4mm2 detected by IVUS was also considered severe. IDF criteria were used to define Metabolic Syndrome and T2DM diagnosis was defined according to the American Diabetes Association criteria. Student's t-test and Pearson Chi-square were used for statistical analysis, considering p < 0.05 statistically significant. Results and discussion The majority of T2DM patients presented severe arterial lesions (74% vs 22%, p<0.001). Using CA procedure, 12% of T2DM had moderate obstructions, compared to 38% of the non-diabetic group (p< 0.05). 8% of patients with moderate lesions by CA were diagnosed with a luminal area less than 4mm2 using IVUS. This luminal area was significantly smaller in the T2DM group than in the control group (3.8mm2 ± 2.42. vs 4.6mm2 ± 2.58, p = 0.03). Conclusion Patients with MS and T2DM submitted to angiography and IVUS, had more severe coronary lesions compared to MS patients without diabetes. This finding suggests that beyond insulin resistance that is present in MS, hyperglycemia may also play a role in the development of atherosclerotic disease. IVUS was useful for diagnosing 8% of severe cases initially considered to be moderate obstructions when using just CA in this scenario.